Checklist of freshwater fishes collected from Ernakulam District, Kerala, India - K.S.J. Beevi; A. Ramachandran (Journal of Threatened Taxa, 2009)
A study has been conducted on the freshwater fishes of Ernakulam district, Kerala. Fishes were collected from the three rivers: Chalakkudy, Muvattupuzha and Periyar using cast net and scoop net. 69 species of fishes belonging to 8 orders, 20 families and 35 genera were collected. The systematic positions of the species collected were also studied. Rare species like Danio fraseri Hora and Mukerji, Esomus malabaricus Day, Wallago attu (Bloch and Schneider), Heteropneustus fossilis (Bloch) and Chela dadiburjori (Menon) could be collected during the study.